Pre‐hospital and In‐hospital Delays After Onset of Acute Ischemic Stroke—A Hospital‐based Study in Southern Taiwan - Chun‐Hung Chen (Kaohsiung Journal of Medical Sciences, 2007)
The biggest hurdle for early hospital presentation is the narrow therapeutic window after stroke. The aims of our study were to investigate the time lags and the factors causing pre‐hospital and emergency department (ED) delay during acute ischemic stroke attack. Between June 2004 and October 2005, we prospectively studied 129 acute ischemic stroke patients who presented to the ED of the study hospital within 4 hours after symptom onset. Chi‐square testing for trend, uni‐variate and multiple logistic regression analyses was performed to evaluate the factors influencing delays in the ED presentation of acute ischemic stroke patients. The median time from symptom onset to ED arrival was 71 (mean ± SD, 82.7 ± 57.7) minutes. The median times from ED arrival to neurologic consultation, computed tomography scan, electrocardiogram, and laboratory data completion were 10 (11.3±9.9) minutes, 17 (9.6±11.3) minutes, 14 (23.3±55) minutes, and 39 (44.4±24.5) minutes, respectively. Univariate and multiple logistic regression models revealed that age < 65 years, illiteracy and awakening with symptoms were the most significant factors related to a delay in ED presentation. This study indicates that 2 hours of pre‐hospital delay is the cutoff point for thrombolytic therapy. Organization of a stroke team and standardized stroke pathways may help to shorten in‐hospital time consumption. Educational efforts should not only focus on the public, but also on the training of ED physicians and other medical personnel.